A Simple Synthesis of Higher Refractive Index Polymeric Nanocomposite Containing the Pendant ZnS Nanocrystals Capping Different Amount of Mercaptoethanol. (11th August 2020) - Li, Xinxin; Xu, Jinku
Abstract : In this paper, three kinds of ZnS NPs capping different amount of mercaptoethanol (ME) were synthesized, and the effect of capping amount on ZnS NPs was studied, indicating that the capping amount of ME on ZnS surface decreases, while ZnS size increases as the decrease of added capping agent in synthesis process, and ZnS NP capping middle amount of ME ( 27.7 wt%) shows a highest apparent refractive index (RI) value. ZnS NPs were composited into polymeric matrices by a simple "one-step" thermocuring method characterized by adding a small amount of functional monomer of glycidyl methacrylate (GMA) and solvent of N, N-dimethylformamide (DMF) The reaction mechanism, studied by 1 H NMR spectra, indicates that the epoxy of GMA monomer can be easily opened and chemically grafted on ME-capped ZnS surface under the catalysis of DMF, and then copolymerized with other monomer. By the route, ZnS NPs can be composited into pure poly(N, N-dimethylacrylamide)-type (DMA-type), DMA-type copolymer, and DMA-free matrices to fabricate transparent films, and its RI value can be improved by either optimizing capping amount on ZnS surface or increasing ZnS content in the nanocomposites. The RI value of resulting dried nanocomposites can be improved to 1.764 by compositing 80 wt% ZnS capping middle amount of ME.